2018
DOI: 10.1016/j.bjm.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence and β-lactamase encoding genes in Enterobacter aerogenes and Enterobacter cloacae clinical isolates from Brazil

Abstract: Enterobacter cloacae and E. aerogenes have been increasingly reported as important opportunistic pathogens. In this study, a high prevalence of multi-drug resistant isolates from Brazil, harboring several β-lactamase encoding genes was found. Several virulence genes were observed in E. aerogenes, contrasting with the E. cloacae isolates which presented none.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…In the genus Enterobacter, some differences in pathogenicity could be noted between E. aerogenes and E. cloacae (149). Azevedo et al reported the presence of virulence-encoding genes in E. aerogenes that have been identified in Klebsiella pneumoniae (149).…”
Section: Clinical Aspects Pathogenicitymentioning
confidence: 99%
“…In the genus Enterobacter, some differences in pathogenicity could be noted between E. aerogenes and E. cloacae (149). Azevedo et al reported the presence of virulence-encoding genes in E. aerogenes that have been identified in Klebsiella pneumoniae (149).…”
Section: Clinical Aspects Pathogenicitymentioning
confidence: 99%
“…Information on the genes associated to virulence is detailed especially for Klebsiella spp., where a number of genes associated to harmful traits were identified, such as those encoding adhesins, siderophores (e.g., enterobactin, aerobactin, yersiniabactin), protectines, or invasins (responsible for mucoid phenotype and invasiveness), and involved in allantoin metabolism [7,11]. For other NECE genera, such as Enterobacter, Cronobacter, and Citrobacter, the knowledge of the genetic determinants associated to virulence and invasiveness is less comprehensive and, with few exceptions (e.g., Citrobacter koseri), mainly acquired from better characterized pathogens [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Macrocolony is well described and accepted as a biofilm model. Usually, studies evaluate macrocolonies’ structure and morphology, like the presence of wrinkle and ring patterns that are related with cellulose and curli fimbriae production, respectively [28,29,42,43,44,45,46]. As far as we know, Richer et al (2014) were the first to investigated different subpopulations/regions generated by macrocolony [47].…”
Section: Discussionmentioning
confidence: 99%
“…For macrocolonies’ growth, a volume of 3 uL of these cultures was spotted on LB agar plates supplemented with Congo Red (40 mg/L) and Coomassie Brilliant Blue (20 mg/L). The plates were incubated at 35 °C for 5 days [42,47].…”
Section: Methodsmentioning
confidence: 99%